Service Quality Evaluation and Farmer Satisfaction in Agribusiness Entrepreneurship Training Programs - Zumi Saidah; Eliana Wulandari; Hepi Hapsari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study evaluates service quality and farmer satisfaction in agribusiness-oriented entrepreneurship training programs for corn farmers. The research focuses on identifying gaps between farmers’ expectations and perceptions of training services across five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. A survey was conducted with 100 corn farmers who had participated in entrepreneurship training programs in Majalengka Regency, Indonesia. Data were analyzed using a modified SERVQUAL instrument integrated with Importance–Performance Analysis (IPA) and the Customer Satisfaction Index (CSI) to assess service performance and determine priority areas for improvement. The results indicate that, overall, farmers report a high level of satisfaction with the training programs, as reflected by a CSI value of 85.99 percent. However, the IPA results reveal that responsiveness of trainers and the adequacy of physical facilities remain key areas requiring improvement, as these dimensions exhibit relatively lower performance compared to their perceived importance. In contrast, assurance and empathy demonstrate strong performance and should be maintained to support training effectiveness. This study contributes to agribusiness management literature by providing an evaluative framework for assessing entrepreneurship training quality and participant satisfaction in smallholder farming contexts. Practically, the findings offer managerial and policy insights for training providers and agricultural extension agencies in designing more responsive, well-supported, and sustainable entrepreneurship training programs for corn farmers. Keywords: service quality, farmer satisfaction, entrepreneurship training, agribusiness management, corn farmers